Comprehensive genomic and transcriptomic analyses of the anaerobic degradation of microcystin in Alcaligenes faecalis D04 - Fei Yang; Lili Yang; Jia Wei; Tian Ma; Mengna Zhou; Liwen Liao; Junhao Xie; Pengji Zhou (Ecotoxicology and Environmental Safety)
Microcystin LR (MC-LR) pollution is a serious threat to aquatic ecosystems and public health in China and is an environmental problem that urgently needs to be solved. However, few studies have investigated the anaerobic degradation pathway and related molecular biological mechanisms of MC-LR. In this study, a bacterium capable of degrading MC-LR with a degradation efficiency of 0.303 µg/mL/d under anaerobic conditions was isolated from water. The strain was identified as Alcaligenes and named Alcaligenes faecalis D04. Two new anaerobic degradation products, one pentapeptide (Adda-Glu-Mdha-Ala-Leu) and one tripeptide (Adda-Glu-Mdha), were identified by chromatography and mass spectrometry, and two new anaerobic degradation pathways for microcystins were proposed. This study revealed a new connection between related functional genes (mblH, ridA, paaA, livI, soxR, gltD, marR, etc.) and bacterial degradation functions through the analysis of multiomics data. Real-time quantitative PCR analysis verified that the expression trends of the differentially expressed genes were consistent with the transcriptomic data. Our study aimed to elucidate the anaerobic degradation pathway and molecular regulatory mechanism of MC-LR in Alcaligenes faecalis D04, which offers important practical significance for microbial strategies to prevent and regulate microcystin contamination.